Firm Training - Dan A. Black; Lars Skipper; Jeffrey A. Smith (Center for Economic Studies and ifo Institute (CESifo), 2023)
Workers acquire skills through formal schooling, through training provided by governments, and through training provided by firms. This chapter reviews, synthesizes, and augments the literature on the last of these, which has languished in recent years despite the sizable contribution of firm training to the overall stock of worker human capital. We engage with research on the determinants of receipt of firm training, the effects of firm training on workers outcomes, and various policy debates related to firm training, including training taxes, training subsidies, non-compete agreements, and the minimum wage. Our discussion emphasizes the complex measurement issues associated with firm training and the interplay of applied theory and applied econometrics in the related empirical literature.
Keywords: I20; I24; J24; J42; J31; 330; training; human capital; firm; worker; classroom; learning by doing; monopsony; minimum wage; training tax; non-compete